2005
DOI: 10.1097/01.opx.0000168588.63897.0f
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Discontinuations With Rigid and Soft Hyper Dk Contact Lenses Used for Continuous Wear

Abstract: Practitioners should anticipate fewer adverse events with rigid versus soft lenses prescribed for continuous wear. Experienced wearers are less likely to discontinue compared with neophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 14 publications
0
33
1
Order By: Relevance
“…10,32 The majority of discontinuations were the result of vision-related problems and only one subject discontinued as a result of comfort-related issues, which occurred during the DW phase of the study. It is difficult to compare success rates between different bifocal/multifocal lens studies as a result of differences in study design and definitions of success.…”
Section: Figurementioning
confidence: 98%
“…10,32 The majority of discontinuations were the result of vision-related problems and only one subject discontinued as a result of comfort-related issues, which occurred during the DW phase of the study. It is difficult to compare success rates between different bifocal/multifocal lens studies as a result of differences in study design and definitions of success.…”
Section: Figurementioning
confidence: 98%
“…However, we envisage that it might be sufficiently powered to detect differences in incidence rate between the two groups, as previous studies with samples sizes similar to those used in the present study have effectively demonstrated differences in incidence rate for different contact lens types and wearing regimes. 27,29 The primary outcome measure of this study is, however, to compare in white European myopic children axial length growth following OK and SV lens wear over a 2-year period. In this respect, the comparison of axial growth between the two groups is optimized by the use of non-contact partial coherence interferometry, which has a resolution that is an order of magnitude better than that of the 10 Hz ultrasound technique.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of adverse events and discontinuations were adapted from Morgan et al 27 Adverse events were classified as "serious," "significant," or "non-significant" according to table 3. 27,28 Although table 3 shows most of the ocular adverse events that could occur as a result of contact lens and spectacle wear, all adverse events, even those not shown in table 3, were recorded in this study. For obscure adverse reactions, the opinion of the ophthalmologist on duty at the clinic is sought and the condition treated in collaboration with the MCOS clinician.…”
Section: Figurementioning
confidence: 99%
“…• 671.5 patient per years of wear was aggregated for CW for 22 days or more • 56.9 patient per years of wear aggregated for EW for 14 to 21 days • 30.0 patient per years of wear aggregated for EW for 7 to 13 days • 26.0 patient per years of wear aggregated for EW for 1 to 6 days • 12.1 patient per years of wear aggregated for no EW or CW wear.…”
Section: Cumulative Patient Per Years Of Lens Wearmentioning
confidence: 99%
“…Ichijima and Cavanagh 21 described that hyper-Dk/t RGP lenses mathematically supply more oxygen than the same-Dk/t silicone hydrogel lenses when taking into account the total area of cornea covered by the CL. Morgan et al 22 and Maldonado-Codina et al 23 reported better clinical performance with Menicon Z-alpha lens design in comparison with silicone hydrogel lenses when worn on a CW basis over a 12-month period. Lakkis et al 24 reported nonserious complications during a study of 6 months duration using a bifocal RGP CL for CW also manufactured in Menicon Z material.…”
mentioning
confidence: 98%